Improvement of Myocardial Cell Injury by miR-199a-3p/mTOR Axis through Regulating Cell Apoptosis and Autophagy - Weixiong Wu; Xingfeng Chen; Qingyang Hu; Xuefei Wang; Jingyu Zhu; Qianzhen Li (Journal of Immunology Research)
Background. Myocardial ischemia-reperfusion injury (MIRI) is characterized by its high incidence rate and mortality. miR-199a-3p is thought to be strongly linked with the development of some myocardial diseases, but the influence of miR-199a-3p in MIRI remains unclear. Methods. AC16 cells were used. The concentrations of mammalian target of rapamycin (mTOR), light chain 3 II/light chain 3 I, and Beclin-1 were detected with western blotting and qRT-PCR. The binding site between mTOR and miR-199a-3p was evaluated via luciferase report assay. Cell apoptosis was evaluated through flow cytometry. Results. Knockdown of miR-199a-3p accelerated the myocardial cell injury after L-oxygen treatment. Increased expression of mTOR and suppressed autophagy were observed after knockdown of miR-199a-3p. Knockdown of miR-199a-3p or overexpression of mTOR greatly aggravated cell injury through inhibiting autophagy. Conclusions. This study might be helpful for the therapeutic method of MIRI through by regulating miR-199a-3p/mTOR.